Life cycle assessment-based urban energy structure optimization: Model estab-lishment and scenario analysis - Chen, Chen; Su, Meirong (Journal of Environmental Accounting and Management, 2026)
Energy structure optimization is vital for urban sustainable development. In this study, a multi-objective model is developed to allocate various energy resources in various urban sectors under various scenarios, aiming to minimize the total system cost, environmental impact, and energy consumption. The environmental impact incurred during the energy lifecycle, including energy production, transportation, and consumption, is evaluated using the lifecycle assessment method. The economic loss of environmental pollution during the energy lifecycle is also incorporated in the economic objective. The model is applied to Beijing, in which four energy resources (coal, oil, natural gas, and electricity) are distributed among six sectors (agriculture, industry, construction, transportation, commerce, and household). Three scenarios are formulated from the base case scenario: i.e., the energy structure adjustment scenario, the energy structure adjustment with low carbon emission scenario, and the energy structure adjustment with low carbon emission and industrial structure adjustment scenario. The results indicate a decline in the proportion of coal to total energy consumption and an increase in the corresponding proportion for the other resources. It is concluded that further increasing the utilization of natural gas and electricity while reducing coal consumption, controlling energy consumption in industry, and strengthening carbon emission restrictions will help achieve more effective and eco-friendly energy use patterns based on a comparison of the environmental impact and economic loss of pollution under all scenarios. The optimization model could provide support for the planning and management of urban energy systems.